Making sense of DSM-5 mania with depressive features. (June 2015) - Reinares, María; del Mar Bonnín, Caterina; Hidalgo-Mazzei, Diego; Undurraga, Juan; Mur, Maria; Nieto, Evaristo; Sáez, Cristina; Vieta, Eduard
Objective: The assessment of the depressive component during mania has become critical for the accurate diagnosis of mixed states, which were defined very narrowly in the past classification systems before Diagnostic and Statistical Manual of Mental Disorders (5th ed.). The aim of this study was to compare socio-demographic, clinical and therapeutic characteristics, as well as clinical and functional outcomes, between manic patients with and without mixed features to validate the relevance of the Diagnostic and Statistical Manual of Mental Disorders (5th ed.) mixed specifier. Methods: This is a subanalysis of a multicentre naturalistic study MANía Aguda y COnsumo de Recursos (acute mania and health resource consumption [MANACOR]) on the burden of mania in bipolar patients from four hospitals in Catalonia (Spain). The sample consisted of 169 adult patients presenting a manic episode and systematically assessed during a 6-month period. Results: A total of 27% ( n  = 46/169) of manic patients showed mixed features. Total number of episodes ( p  = 0.027), particularly depressive and mixed, was greater in manic patients with mixed features, as well as depressive onset ( p  = 0.018), suicide ideation ( p  = 0.036), rapid cycling ( p  = 0.035) and personality disorders ( p  = 0.071). In contrast, a higher percentage of pure manic subjects were inpatients ( p  = 0.035), started the illness with mania ( p  = 0.018) and showed family history of bipolar disorder ( p  = 0.037), congruent psychotic symptoms ( p  = 0.001) and cannabis use ( p  = 0.006). At baseline, pure manic patients received more risperidone ( p  = 0.028), while mixed patients received more valproate ( p  = 0.049) and antidepressants ( p  = 0.005). No differences were found in syndromic recovery at the end of the study. However, depressive change was higher in the mixed group ( p  = 0.010), while manic change was higher in the pure manic group ( p  = 0.029). At the end of follow-up, the group with mixed features showed a significant trend towards higher psychosocial dysfunction. Conclusion: A total of 27% of manic patients showed mixed features. Groups differed regarding clinical characteristics, course of illness, psychosocial functioning, prescribed treatment and symptom progress. Depressive symptoms in mania should be routinely assessed and considered to guide treatment.